Application of cognitive and metacognitive learning strategies in teaching of economic discourse in the target english language - Olga Dzhagatspanyan (Universidade Estadual Paulista, 2021)
The article surveys cognition and metacognition as a strain of language learning strategies and illustrates the significance of comprising them in the teaching of economic discourse. The research's relevance is that metacognitive and cognitive strategies have not been thoroughly researched and analyzed in the economic discourse teaching process. The paper aims to identify techniques that apply metacognitive and cognitive strategies to make the economic discourse learning process more accessible and enthralling. The work identifies the percentage of favorable results of involvement language learning strategies into the economic discourse learning process. We recognize the importance and necessity of using metacognition and cognition in knowledge obtaining procedure using traditional and nontraditional teaching methods. Evaluating the economic faculty students' English studies in the character of the target language, we denote the significant factors that the use of the learning strategies helps them find the most objective formula for comprehension of any phenomenon individually. The survey analysis shows that the classes retraining metacognitive and cognitive language learning strategies are more captivating for the students and evoke an eloquent comprehension of any issue. The use of metacognitive and cognitive teaching techniques makes a complete cognition of the phenomenon that can even be unclear in the native language.